2017
DOI: 10.18632/oncotarget.17444
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of delayed intracerebral hemorrhage after ventriculoperitoneal shunt insertion

Abstract: BackgroundDelayed intracerebral hemorrhage after ventriculoperitoneal (VP) shunt insertion is rare and has not been well investigated previously. Its characteristics is still unknown.ObjectiveWe reported 12 patients with delayed intracerebral hemorrhage after VP shunt to investigate the potential risk factors and the outcome.Results12 patients (1.59%) of all the 754 hydrocephalus had delayed intracerebral hemorrhage after VP shunt insertion. 4 patients were women and 8 patients were men, ranging in age from 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 9 publications
(18 reference statements)
0
11
2
Order By: Relevance
“…As for our study, we excluded the patients with anticoagulant or antiplatelet therapy in order to control the confounding factors, and we found that preoperative PT, APTT, INR and PLT were not risk factors for DICH. Two articles presented that postoperative manipulation of valve system might be a risk factor for DICH secondary to VP shunt 4,15 , which was not supported (P = 0.382) in our study either.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…As for our study, we excluded the patients with anticoagulant or antiplatelet therapy in order to control the confounding factors, and we found that preoperative PT, APTT, INR and PLT were not risk factors for DICH. Two articles presented that postoperative manipulation of valve system might be a risk factor for DICH secondary to VP shunt 4,15 , which was not supported (P = 0.382) in our study either.…”
Section: Discussioncontrasting
confidence: 84%
“…Nevertheless, this difference was not found in our study (P = 0.674). Advanced age, history of craniotomy were considered to be the risk factors for DICH secondary to VP shunt in several articles [15][16][17][18] , and these factors might increase the fragility of cerebral tissue. However, one article published in 2017 reported that there was no difference between two groups with respect to age 17 .…”
Section: Discussionmentioning
confidence: 99%
“…DICH is one of complications of VP shunt surgery and was first reported in 1985 17 . It was considered to be a rare complication with incidence varies from 0.4 to 4% 4 , 5 , 8 , 9 , 18 . However, the incidence might be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this difference was not found in our study. Advanced age, history of craniotomy were considered to be the risk factors for DICH secondary to VP shunt in several articles 8 11 , and these factors might increase the fragility of cerebral tissue. However, one article published in 2017 reported that there was no difference between two groups with respect to age 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation